Characteristics of the flame flashback in a dual-mode scramjet combustor by the gliding arc plasma - Rong Feng; Jiajian Zhu; Dongze Li; Zhipeng Meng; Mingbo Sun; Hongbo Wang; Chenglong Wang; Chao Wang; Zhenguo Wang (Applications in Energy and Combustion Science, 2023)
A multi-channel gliding arc (MCGA) plasma with an average power of 6000 W is utilized to control the flame flashback in a dual-mode scramjet combustor with a cavity flameholder. Optical measurements, including synchronous high-speed CH* emissions and high-speed schlieren, simultaneous high-speed camera with the oblique view and high-speed CH* emission, accompanied by the three-dimensional RANS simulation, were employed to characterize the flame flashback with or without the MCGA plasma. The results show that a typical flame flashback cycle can be observed with a period of ∼2 ms in the combustor. The back pressure reduced by the dynamic heat release of the reaction zone is not sufficient to form the steady thermal choking in the mainstream in the absence of the MCGA, which results in the oblique shocks and bow shocks appearing in dual-mode scramjet combustion. When the plasma is added, the flame is strengthened near the plasma region, and the combustion oscillation is suppressed significantly. The re-ignition and attachment characteristics of the MCGA plasma provide the new flame kernels to the mainstream flame, and the leading edge of the mainstream flame follows the MCGA plasma. Due to the relatively stable heat release near the fuel jet assisted by the plasma, the thermal choking is stable presented in the combustor with bow shocks by higher back pressure, indicating that the combustion oscillation is suppressed by the MCGA plasma in the dual-mode scramjet combustor.